If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (W + -7)(w + 5) = 0 Reorder the terms: (-7 + W)(w + 5) = 0 Reorder the terms: (-7 + W)(5 + w) = 0 Multiply (-7 + W) * (5 + w) (-7(5 + w) + W(5 + w)) = 0 ((5 * -7 + w * -7) + W(5 + w)) = 0 ((-35 + -7w) + W(5 + w)) = 0 (-35 + -7w + (5 * W + w * W)) = 0 (-35 + -7w + (5W + wW)) = 0 Reorder the terms: (-35 + 5W + -7w + wW) = 0 (-35 + 5W + -7w + wW) = 0 Solving -35 + 5W + -7w + wW = 0 Solving for variable 'W'. Move all terms containing W to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 5W + -7w + 35 + wW = 0 + 35 Reorder the terms: -35 + 35 + 5W + -7w + wW = 0 + 35 Combine like terms: -35 + 35 = 0 0 + 5W + -7w + wW = 0 + 35 5W + -7w + wW = 0 + 35 Combine like terms: 0 + 35 = 35 5W + -7w + wW = 35 Add '7w' to each side of the equation. 5W + -7w + 7w + wW = 35 + 7w Combine like terms: -7w + 7w = 0 5W + 0 + wW = 35 + 7w 5W + wW = 35 + 7w Reorder the terms: -35 + 5W + -7w + wW = 35 + 7w + -35 + -7w Reorder the terms: -35 + 5W + -7w + wW = 35 + -35 + 7w + -7w Combine like terms: 35 + -35 = 0 -35 + 5W + -7w + wW = 0 + 7w + -7w -35 + 5W + -7w + wW = 7w + -7w Combine like terms: 7w + -7w = 0 -35 + 5W + -7w + wW = 0 The solution to this equation could not be determined.
| 13.5*32=x | | 4(y-6)-8y= | | 432=32*w | | -3(x+3)+8=3x+5 | | 5.00+0.16b=11.25 | | -4x+16=-2x-10 | | 19=3a+b | | -4-7n=2-7n-6 | | 15s+24=8(10+3x)-2 | | 111+11x=-3 | | 5*cos(x+2)=1 | | 2y=.75x-4 | | y=5.5x+30 | | 7-2(3x-1)=2x+5[3(4x-1)+(-2)] | | 3(x-3)=5(1.5-x) | | m+6=13+2m | | y+2y=3 | | 6889*2/.5=x | | 3(x-.25)=2.16 | | 6889*2/.=x | | -7z=-4z^2-3 | | y=x^4-10x^2-3 | | 6.2x-6+x-1.2= | | e^4x-7e^2x+12=0 | | 83*83/2=x | | -4y=-2x+16 | | 5h-9p=9 | | f(x)=x^4-10x^2-3 | | 750=3(5a) | | 2(2x-10)=x-8 | | 83*83=x | | 8t+16-3t-12=6+-34 |